Pengaruh Tingkat Suku Bunga dan Inflasi terhadap Nilai Tukar Dollar Amerika (Pendekatan Model Linier Klasik, Autoregressive, dan Granger) - Ari Christianti (Jurnal Riset Manajemen dan Bisnis, 2008)
This research is empirically examined the factors fficting exchange rate. The examination will employ three models, namely, classical linier model, autoregressive, and granger. The data are drann from Indonesian monthly macro economics indicators, narnely, interest, inflation, and exchange rate. The data'is collected from 2005-2007. The empirical result of this research indicates that the most fficient model is Granger Causality Model. Moreover, the result also find that interest and inflation rate affect the exchanged rate.Keywords: Interest, inflation, exchange rate, classical linier model, autoregressiu.e, and granger causality model